“CLUPS”: A New Culture Medium for the Axenic Growth of Entamoeba histolytica - González Salazar, Francisco; Meester, Irene; Guzmán de la Garza, Francisco Javier; De la Garza Salinas, Laura Hermila; Sampayo Reyes, Adriana; Garza González, Jesús Norberto; Monsivais Diaz, O.; Barba Dávila, B. A.; Hernández García, Magda Elizabeth; Vargas Villarreal, Javier (Hindawi Publishing Corporation, 2018)
Amebiasis remains a major health problem in Mexico. Terefore, the search for better culture media and low-cost diagnostic and therapeutic tools is fundamental. We present a new culture medium for Entamoeba histolytica which allows the microbe to preserve its virulence factors and ability to induce hepatic abscesses in animal models. Te novel CLUPS medium is an improved version of the PEHPS medium, previously designed in our laboratory. Te main diference is the substitution of raw beef liver in PEHPS by raw beef lung in the CLUPS medium. To compare the performance of three-culture media (traditional TYI-S-33, PEHPS, and CLUPS), E. histolytica trophozoites were cultured in quintuplicate, followed by the evaluation of phospholipase activity and the induction of liver abscesses in golden hamsters. E. histolytica trophozoites grew signifcantly better in CLUPS medium than in TYIS-33. Likewise, CLUPS-cultured trophozoites produced signifcantly more phospholipases than TYI-S-33-cultured trophozoites. Finally, trophozoites grown in any of the three tested media had similar potential to induce liver abscesses